Studies of a modulated Hall thruster. (21st May 2021) - Simmonds, Jacob; Raitses, Yevgeny; Smolyakov, Andrei; Chapurin, Oleksandr
Abstract: A typical Hall thruster is powered from a DC power supply and operates with a constant discharge voltage. In operation, the discharge current is subject to strong low frequency oscillations (so-called breathing oscillations). Recent studies have shown that not only can these breathing oscillations be correlated with improved performance, but these oscillations can be induced and controlled by modulating the anode voltage. In this work, a systematic experimental study of the plasma flow in a modulated cylindrical Hall thruster was performed to characterize the effect of natural and modulated breathing oscillations on thruster performance. Measurements suggest that modulating the anode voltage in resonance with the natural breathing frequency does increase the thrust, but a corresponding phase alignment of discharge current and discharge voltage causes the efficiency gains to be insignificant. In addition, the outward shift of the acceleration region causes the plasma plume divergence to increase at the resonance condition and thereby, limit the thrust increase. Mechanisms underlying the relative phase between discharge current, ion current, and discharge voltage are investigated experimentally and corroborated with one-dimensional hybrid simulations of the thruster discharge.